Pengembangan Keterampilan Mengajar Guru Berbasis Nilai-nilai Pendidikan Agama Islam - Diah Verra Ninda; Riski Ananda; Dzil Ilman Azra; Sukatin; Pahmi (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2022)
Teaching skills are teaching abilities that must be possessed by teachers. The method used is library research. data collection in research is carried out by examining and exploring from books, journals, documents (both printed and electronic), as well as other sources of data and information that are considered relevant to research or studies. Teaching skills consist of 8 components, namely opening skills and closing lessons, explaining skills, varying skills, strengthening skills, asking questions, managing classes, teaching small groups and individuals, and guiding small group discussions. aims to enable teachers to carry out their teaching duties effectively, efficiently and professionally, as well as guide students to be mentally prepared, think critically, easily understand lessons and be motivated. Integrating the values ??of Islamic education in guided teaching skills is basically forms of behavior or abilities that are specific or professional and fundamental to carrying out noble tasks in a guided manner in obtaining professional and Islamic teachers.